Comparación de la capacidad antioxidante in vitro de extractos de hojas de uncaria tomentosa “uña de gato” procedente de la provincia de Moyobamba (Region San Martin) y la provincia de Virú (campamento San Jose - Chavimochic - Region La Libertad - Cruzado Reyes, Camilo Alberto (2007)
The main objective of the present investigation work is to compare the capacity antioxidante of the extracts of leaves of Uncaria tomentosa, “cat's claw” coming from the province of Moyobamba (Region San Martin) and in the province Virú - Chavimochic (Region La Libertad). This study in Vitro was carried out with the extracts metanólic and etanólic of the leaves of Uncaria tomentosa of the mentioned towns The capacity antioxidante was determined facing this extracts with a solution from DPPH to the concentration of 80mg/mL and read to a wavelength of 517nm. The biggest capacity antioxidante presents it the extracts metanólics and etanólics of the province of Moyobamba (Region San Martin).